Development of a Booklet for Introduction to Types of Emotions in Preschool Children - Anegayuda, Yugen Ghifari; Araminta, Rifani Alya; Uranus, Hanna Christina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to develop an emotion recognition booklet for preschoolers based on Paul Ekman's (1972) basic emotion types. This research uses the Research & Development (R&D) method with ADDIE instructional design. Validation by experts showed that the booklet is 100% very valid and feasible to use to support emotional learning in early childhood in preschool, Before the use of the booklet, children only recognize some basic emotions such as angry and sad. After using the booklet, they can identify six basic emotions and connect the expression of emotions with triggers in daily life. The booklet is designed with simplified sentences and attractive visuals, using an interactive approach.